Effectiveness of Lemon Aromatherapy-Enhanced Health Belief Model Counseling in Reducing Labor Pain - Eka Ristin Tarigan; Siti Nurul Fadhilah Sari; Adriana Bangun; Adelina Fitri Tanjung; Putri Nadilla; Jihan Anggraini (Media of Health Research, 2025)
Background: Labor pain is a complex sensory-emotional experience that may lead to maternal exhaustion and prolonged labor if inadequately managed. Health Belief Model (HBM)-based antenatal counseling may improve coping self-efficacy, while inhaled lemon (*Citrus limon*) aromatherapy may reduce pain perception. **Objective:** To evaluate the effectiveness of lemon aromatherapy-enhanced HBM counseling in reducing labor pain and distinguish the effects of counseling from aromatherapy. Methods: A three-arm quasi-experimental study was conducted among 135 low-risk laboring women in Medan, Indonesia. Participants received HBM counseling plus lemon aromatherapy (n=45), HBM counseling only (n=45), or routine care (n=45). Pain intensity was measured at cervical dilatations of 4, 6, and 8 cm using the Numeric Rating Scale. Data were analyzed using ANOVA, post-hoc tests, relative risk, and generalized estimating equations. Results: At 8 cm dilatation, mean pain scores were 6.5±1.4, 7.8±1.3, and 8.3±1.2 in Groups A, B, and C, respectively. Aromatherapy significantly reduced pain compared with counseling alone (p<0.001). Group A also demonstrated lower severe pain risk (adjusted RR=0.38; 95% CI: 0.22–0.66), shorter active labor, and higher birth satisfaction, while neonatal outcomes were comparable. **Conclusion:** HBM-based antenatal counseling combined with lemon aromatherapy is an effective, safe, and low-cost strategy for improving labor pain management in primary midwifery care.